A Study on financial distress of firms - Son, Young-Chang (KDI School, 2000)
This thesis analyzes financial distress of firms from the financial point of view through a case study of Midopa Department Store which went bankrupt in 1998. Financial distress of firms throughout the world is a frequent occurrence with important implications to many stakeholders. In Korea since the IMF crisis, people have experienced great hardship due to financial distress of firms. Financially distressed firms can either be restructured and successfully emerge as continuing entities or be liquidated for the benefit of creditors before their asset value is dissipated. The treatment of financially distressed firms, however, does not entirely depend on financial analysis. Political consideration, long-term economic plan, and the social atmosphere including reaction of labor union are implicitly or explicitly involved in the process. This thesis examines the implications of financial distress by analyzing the causes and possible restructuring options of Midopa Department Store.
Thesis(Master) --KDI School:Master of Business Administration,2000